To solve the system of equations given by:
- \( 2x - y = 1 \) (Equation 1)
- \( -3x + y = -5 \) (Equation 2)
Let's solve these equations step-by-step.
From Equation 1:
- Rearranging for \( y \): \[ y = 2x - 1 \]
Now substitute \( y \) in Equation 2:
- Substitute \( y \) into Equation 2: \[ -3x + (2x - 1) = -5 \] \[ -3x + 2x - 1 = -5 \] \[ -x - 1 = -5 \] \[ -x = -5 + 1 \] \[ -x = -4 \] \[ x = 4 \]
Now substitute \( x = 4 \) back into \( y = 2x - 1 \) to find \( y \):
- Calculate \( y \): \[ y = 2(4) - 1 \] \[ y = 8 - 1 \] \[ y = 7 \]
Thus, the solution to the system of equations is \( (4, 7) \).
The correct answer from the options provided is:
B. (4, 7).